Ocenjevanje temperamenta v zgodnjem mladostništvu: psihometrične značilnosti vprašalnika EATQ-R-SF - Kranjec, Eva; Zupančič, Maja; Sočan, Gregor (Revija za elementarno izobraževanje, 2021)
Measurement of Early Adolescents’ Temperament: Psychometric Characteristics of the EATQ-R-SF. The study explored the psychometric characteristics of the Revised Early Adolescent Temperament Questionnaire (EATQ-R-SF). Based on data of 238 early adolescents, we examined the factor structure of the EATQ-R-SF, reliability, and gender differences in mean levels of trait scores. The results showed a satisfactory fit to the models, although the fit indices for some subscales did not reach the recommended values. Internal consistency of the scales was satisfactory. Girls exhibited higher levels of fear, pleasure sensitivity, affiliation and positive emotionality than boys. The reliability of scores was appropriate for use in research, although it would need further improvement.
Keywords: temperament; early adolescence; questionnaire EATQ-R-SF; psychometric proprerties; gender differences